Association of Virtual Nursing and Task Completeness: An Observational Study - Saif Khairat; Jennifer Morelli; Julia Aucoin; Barbara S. Edson; Cheryl B. Jones; Christopher M. Shea (SAGE Open Nursing)
Introduction Higher nurse turnover rates are associated with lower care quality and worse patient and nurse outcomes. Healthcare systems nationwide are implementing virtual nursing (VN), an innovative nursing care model, to reduce nurse turnover. However, there is a lack of evidence regarding the association between VNs and Electronic Health Record (EHR) documentation completeness and care services provided. Methods This cross-sectional study examined the association between using VN and documentation completeness and care provided. This mixed-methods study used observational and qualitative evaluation of a VN care team and bedside unit nurses at a major Southeastern hospital in the United States (US). Data collection included direct observation and semi-structured interviews. Post-observation interviews were conducted with VNs and unit nurses to obtain their perception of task completion and their perceived overall efficiency. Results The duration of both admission (9:45 min vs. 15:53 min) and discharge encounters (6:55 min vs. 19:07 min) was longer with VNs, indicating a more lengthy and thorough approach. The study findings show that VN was associated with increased documentation completeness for patient admissions (58.8% completion by bedside nurses, 80.2% completion by VNs) and discharges (67.8% completion by bedside nurses, 80.2% by VNs). Additionally, the interviews emphasized the time-saving benefits of VN, with interviewees acknowledging VN efficiency, communication, and collaboration. Conclusion This observational study contributes to the understanding of the impact of VN on care provision and documentation completeness, shedding light on the potential of VN as an effective strategy for enhancing nursing care in healthcare settings. The study findings provide valuable insights into the potential benefits of VN in improving task completeness and documentation accuracy, addressing some of the challenges posed by nursing shortages and high turnover rates.